Methotrexate: Revisited efficiency and safety of drug administration in psoriasis patients - A. L. Bakulev (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents the current data of the literature on methotrexate, which is now one of the most commonly used preparation for the systemic treatment of patients with moderate to severe psoriasis. The following problems are under consideration: estimation by specialists of response to systemic psoriasis therapy and possible therapeutic strategies; selecting initial doses of methotrexate for the treatment of patients with psoriasis; the possibilities of combined use with genetically engineered biological agents and monitoring of therapy. The data from randomized clinical trials on the long-term continuous treatment with methotrexate (efficacy, safety); methods of its administration to patients and time and criteria for long-term effecasy are reported. There are presented the data on the mechanisms of methotrexate action and the new data about the impact on the adenosine metabolism and the ability of the preparation to modulate the inflammatory response in the skin of patients by inhibiting the cellular components of the inflammatory infiltrate in the skin (dendritic antigen-producing cells and T-lymphocytes), as well as the suppression of expression of some proinflammatory cytokines (IFN-y and IL17A).